Where is Stonehenge? - Kelley, True (Where is (Grosset & Dunlap), 2016)
Where is Stonehenge? That's an easy question to answer. It sits on the Salisbury Plain in Southern England. But what is the meaning of these strange circles of stones? Was Stonehenge a religious site to honor the dead? Or a sacred place of healing? Or perhaps an astrological calendar? These are much harder questions to answer. However, in an engaging and easy-to-read account, True Kelley puts forth all theories--past as well as current ones--about Stonehenge and the people who four thousand years ago managed to build this amazing monument.